2018
DOI: 10.1155/2018/6548715
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Peripheral Microvascular Endothelial Dysfunction in Rheumatoid Arthritis Patients: A Multicenter Cross-Sectional Study

Abstract: Objectives To define the prevalence and determinants of peripheral microvascular endothelial dysfunction (ED) in a large series of rheumatoid arthritis (RA) patients free of previous cardiovascular events. Materials and Methods Data from 874 RA patients enrolled in the EDRA study (Endothelial Dysfunction Evaluation for Coronary Heart Disease Risk Estimation in Rheumatoid Arthritis—ClinicalTrials.gov: NCT02341066) were analyzed. Log-transformed reactive hyperemia index (Ln-RHI) was evaluated by peripheral arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 39 publications
(48 reference statements)
1
24
0
1
Order By: Relevance
“…The studies revealed a weak correlation between microvascular and macrovascular endothelial dysfunction in RA patients. Microvascular endothelial dysfunction results from the interaction between inflammation, immune dysregulation, and traditional cardiovascular risk factors, representing a significant factor related to accelerated atherosclerosis and future cardiovascular events in RA patients [31].…”
Section: Macro-and Microvascular Endothelial Dysfunctionmentioning
confidence: 99%
“…The studies revealed a weak correlation between microvascular and macrovascular endothelial dysfunction in RA patients. Microvascular endothelial dysfunction results from the interaction between inflammation, immune dysregulation, and traditional cardiovascular risk factors, representing a significant factor related to accelerated atherosclerosis and future cardiovascular events in RA patients [31].…”
Section: Macro-and Microvascular Endothelial Dysfunctionmentioning
confidence: 99%
“…Rheumatoid arthritis is associated with higher mortality compared to the general population Endothelial dysfunction is common in rheumatoid arthritis and affects both macrovascular and microvascular beds [66,67]. In particular, microvascular endothelial dysfunction affects approximately 33% of patients even in the absence of overt cardiovascular disease [61]. This might account for the reduced coronary flow reserve, and consequent increased risk of ischaemic heart disease, reported in patients with rheumatoid arthritis and other similar autoimmune conditions [68].…”
Section: Rheumatoid Arthritis: a Human Model Of Premature Vascular Agmentioning
confidence: 99%
“…The excess mortality in rheumatoid arthritis is primarily due to cardiovascular death, with a standardized mortality ratio of 1.46 compared to the general population[60]. It is postulated that the state of chronic systemic inflammation in rheumatoid arthritis, and the activation of pro-atherosclerotic cytokines such as TNF-, interleukin 1 (IL-1), and interleukin-6 (IL-6), favours endothelial dysfunction, vascular damage and atherosclerosis(Figure 1)[61][62][63][64]. However, traditional risk factors, such as hypertension, diabetes, obesity, and hypercholesterolaemia, also contribute to the pathogenesis of vascular dysfunction and the risk of adverse cardiovascular outcomes in this group[65].…”
mentioning
confidence: 99%
“…A weak correlation was found between micro-vascular ED and body mass, and systolic and diastolic blood pressures, triglycerides (TG), high-density lipoproteincholesterol (HDL-c) and glucose in middle-aged men 8 . RHI was associated with blood pressure and HDL-c in chronic kidney disease and rheumatoid arthritis patients 9,10 . However, a negative pro le also existed: RHI measured the micro-vascular ED, but failed to show the correlations with a risk factor pro le (hypercholesterolemia, hypertension, diabetes, and overweight/obesity) in the asymptomatic population [11][12][13] .…”
Section: Introductionmentioning
confidence: 95%